TINGKAT PENGETAHUAN SISWI TENTANG KANKER SERVIKS DI SMAN 1 NGUTER KABUPATEN SUKOHARJO - Siti Nurjanah (OVUM : Journal of Midwifery and Health Sciences, 2021)
WHO noted that cervical cancer ranks top among various types of cancer that cause death in women in the world. In Indonesia, every year more than 15,000 cases of cervical cancer and about 8000 cases of which end in death. Preliminary study at SMAN 1 Nguter of 10 respondents who only knew about cervical cancer 3, and 7 female students who did not know anything about cervical cancer. This study aims to determine the level of knowledge of female students about cervical cancer at SMAN 1 Nguter Sukoharjo. The type of research methodology used is descriptive quantitative, where the population is all students of SMAN 1 Nguter Sukoharjo and there are 100 respondents with probability sampling technique by simple random sampling, the research instrument using a closed questionnaire. The results of the research that has been carried out on students of SMAN 1 Nguter Sukoharjo can be seen that the knowledge of SMAN 1 Nguter students about cervical cancer, shows the results of good knowledge as many as 15 respondents (15%), sufficient knowledge as many as 63 respondents (63%), and lack of knowledge as many as 22 respondents (22%). Conclusion: The level of knowledge of female students about cervical cancer at SMAN 1 Nguter Sukoharjo is mostly in the sufficient category.